2019
DOI: 10.4078/jrd.2019.26.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Association of Uveitis with Radiographic Progression in Patients with Axial Spondyloarthritis: A Propensity Score Matching Analysis

Abstract: Objective. Acute anterior uveitis (AAU) is the most common extra-articular manifestation in patients with axial spondyloarthritis (axSpA). However, the relationship between AAU and radiographic progression in axSpA remains unclear. Hence, we investigated whether the presence of AAU is associated with radiographic structural damage in patients with axSpA. Methods. Clinical and radiographic data were obtained from 253 patients with axSpA. Radiographic progression over 2 years was assessed using the modified Stok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Several studies have determined clinical parameters that are useful for the prediction of radiographic progression in AS patients [16][17][18]. That is, the presence of syndesmophytes at baseline, increased acute phase reactants, male sex, older age, presence of uveitis, and smoking are considered to be predictors of radiographic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have determined clinical parameters that are useful for the prediction of radiographic progression in AS patients [16][17][18]. That is, the presence of syndesmophytes at baseline, increased acute phase reactants, male sex, older age, presence of uveitis, and smoking are considered to be predictors of radiographic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies failed to demonstrate any association between AAU and radiographic progression in patients with AS [12][13][14] and SpA [15], whereas another study reported that a history of AAU was independently associated with more severe radiographic damage in patients with AS [16]. In contrast to these previous observations, Kim, et al reported that a history of AAU was the only independent variable indicating less severe mSASSS changes in their PS-matched axSpA patients and, interestingly, other variables that have been known to be associated with progression of spinal damage were not found to be significant [10]. Although the reason for this discrepancy is not fully understood, the retrospective design of the study, relatively small number of patients, differences in the AAU prevalence between patient populations, and the possibility of index event bias should be considered when interpreting their results.…”
Section: A Propensity Score Matching Analysis Showed the Significant ...mentioning
confidence: 86%
“…As axSpA includes a vast array of clinical manifestations and progress slowly over the years, the effect of certain clinical parameters on the disease course remain poorly identified. In this regard, the study by Kim et al [10] can be meaningful. This report is the first to evaluate the impact of various clinical variables on mSASSS changes in Korean axSpA patients using PS matching analysis.…”
Section: A Propensity Score Matching Analysis Showed the Significant ...mentioning
confidence: 89%
See 1 more Smart Citation